Intrafracture Recombinant Platelet-Derived Growth Factor Improves Fracture Healing Process on Wistar Rat - I Gusti Ngurah Wien Aryana; Kadek Gede Bakta Giri; I Ketut Suyasa; Anak Agung Wiradewi Lestari (Masters Program in Public Health, Sebelas Maret University, 2023)
Background: Femoral fracture is associated with high morbidity and mortality, especially in young adults with high-energy injuries. Abnormal fracture healing presents as a significant matter in management of femoral fracture. Platelet Derived Growth Factor (PDGFBB) is proposed as potential agent in fracture healing. Up to this point, PDGF has been scientifically studied improve wound healing by enhancing fibroblast proliferation, extracellular matrix synthesis, and revascularization. This study aims to evaluate role of PDGF on fractured bone healing.Subjects and Method: This was a randomized controlled trial conducted at Animal and Biomedical Laboratory of Udayana University, from March to September 2022. 36 male and healthy Wistar Rats at 34 months old and weighs 140160 grams were selected for this study. The dependent variables were Allen score, type I and type III collagen levels. The independent variable was administration of 10 mcg PDGFBB following femoral osteotomy and intramedullary wire fixation. Type I and III collagen levels are assessed using ELISA methods. Statistical analysis is performed using independent T-test in SPSS ver 25.0 software.Results: Allen score in the PDGFBB group (Mean= 3.89; SD= 1.40) was higher than control group (Mean= 2.28; SD= 1.48), with p=0.002. Type I collagen in the PDGFBB group (Mean= 4.97; SD= 0.54) was higher than control group (Mean= 4.41; SD= 0.74), with p=0.014. Type III collagen in the PDGFBB group (Mean= 12.1; SD= 2.49) was higher than control group (Mean= 10.01; SD= 1.61), with p=0.005.Conclusion: In comparison to the nonPDGFBB group, Wistar rats that had their femurs osteotomized and joined with intramedullary wire in the PDGFBB group has higher mean of Allen score, type I and type III collagen levels.Keywords: femoral fracture, allen score, type I collagen, type III collagen, PDGFBBCorrespondence: IGN Wien Aryana, Consultant of Sports Medicine, Dept. Orthopaedic and Traumatology, Prof IGNG Ngoerah General Hospital, Faculty of Medicine, Udayana University. Jl. Diponegoro, Dauh Puri Klod. Denpasar City, Bali 80113. Email: wienaryanaortho@gmail.com. Mobile: +62811385263.Indonesian Journal of Medicine (2023), 08(02): 136141https://doi.org/10.26911/theijmed.2023.08.02.02